ACCULTURATION AND END-OF-LIFE DECISION MAKING: COMPARISON OF JAPANESE AND JAPANESE-AMERICAN FOCUS GROUPS - Bito, Seiji (Bioethics, 2007)
Variation in decision-making about end-of-life care among ethnic groups creates clinical conflicts. In order to understand changes in preferences for end-of-life care among Japanese who immigrate to the United States, we conducted 18 focus groups with 122 participants: 65 English-speaking Japanese Americans, 29 Japanese-speaking Japanese Americans and 28 Japanese living in Japan. Negative feelings toward living in adverse health states and receiving life-sustaining treatment in such states permeated all three groups. Fear of being meiwaku, a physical, psychological or financial caregiving burden on loved ones, was a prominent concern. They preferred to die pokkuri (popping off) before they become end stage or physically frail. All groups preferred group-oriented decision-making with family. Although advance directives were generally accepted, Japanese participants saw written directives as intrusive whereas Japanese Americans viewed them mainly as tools to reduce conflict created by dying person's wishes and a family's kazoku no jo– responsibility to sustain the dying patient. These findings suggest that in the United States Japanese cultural values concerning end-of-life care and decision-making process are largely preserved.